1989
DOI: 10.1038/bjc.1989.380
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody 3F8 recognises the neural cell adhesion molecule (NCAM) in addition to the ganglioside GD2

Abstract: Summary The monoclonal antibody 3F8 has been described as binding to the ganglioside GD2. This antibody, of the IgG3 isotype, has been used in immunotherapy, radioimmunolocalisation and targeted radiation therapy. 3F8 was originally observed to have a binding profile similar to two monoclonal antibodies, UJ13A and 5.1 HI 1, characterised as binding to the neural cell adhesion molecule (NCAM). This observation has also been confirmed using a hetero-antiserum prepared against purified NCAM. The cross-reactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…It was suggested that one such Mab provided a well-needed addition to immunomarkers capable of distinguishing SCLC from non-SCLC, in agreement with our opinion that polyclonal anti-NCAM antibodies could be a useful diagnostic tool. Similarly, the potential therapeutic use of polyclonal anti-NCAM antibodies suggested here, is supported by a recent report [39] describing the use of a Mab, directed against the carbohydrate epitope common to NCAM and the ganglioside GD2 for immunotherapy and targeted radiotherapy. Another of these studies [41] on the SCLC H69 cell line showed the presence of two NCAM isoforms of 180 and 140 kDa and also high levels of polysialic acid, which was suggested to be implicated in the invasive behaviour of these tumors.…”
Section: Resultssupporting
confidence: 72%
“…It was suggested that one such Mab provided a well-needed addition to immunomarkers capable of distinguishing SCLC from non-SCLC, in agreement with our opinion that polyclonal anti-NCAM antibodies could be a useful diagnostic tool. Similarly, the potential therapeutic use of polyclonal anti-NCAM antibodies suggested here, is supported by a recent report [39] describing the use of a Mab, directed against the carbohydrate epitope common to NCAM and the ganglioside GD2 for immunotherapy and targeted radiotherapy. Another of these studies [41] on the SCLC H69 cell line showed the presence of two NCAM isoforms of 180 and 140 kDa and also high levels of polysialic acid, which was suggested to be implicated in the invasive behaviour of these tumors.…”
Section: Resultssupporting
confidence: 72%
“…Recently, the presence of 140-kDa NCAM on ES cell lines was confirmed by FCI with 6H7 and Leu-19 antibodies [24]. A study with Mab 3F8, raised following immunization of mice with neuroblastoma cells and recognizing sialic acid residues epitope of NCAM, showed indirect immunofluorescence reactivity of all four studied cell lines of ES [18]. On the other hand, immunohistochemical studies have generally failed to show NCAM expression in ES tissue.…”
Section: Discussionmentioning
confidence: 98%
“…The observed unexpectedly high affinity of mAb735 for long PSAs was also reflected in the need for rigorous regeneration after binding of MenB polysaccharide in the SPR, as well as in the difficulties in the removal of bound mAb735 from immunoblots of polysialylated NCAM. 1 As some gangliosides have been suggested to cross-react with oligosialic acid antibodies (Patel et al, 1989), the reactivity of their oligosaccharide-analogues, mono-and disialosyl lactose was tested. Although high concentrations (up to 10 mM) of disialyllactose, sialyllactose and lactose were used in the assay, no binding could be demonstrated.…”
Section: Specificity Of the Interactionmentioning
confidence: 99%